2013
DOI: 10.1089/ten.tea.2012.0177
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer Scale Guidance of Mesenchymal Stem Cells to Form Structurally Oriented Cartilage Extracellular Matrix

Abstract: Tissue engineering is a possible method for long-term repair of cartilage lesions, but current tissue-engineered cartilage constructs have inferior mechanical properties compared to native cartilage. This problem may be due to the lack of an oriented structure in the constructs at the microscale that is present in the native tissue. In this study, we utilize contact guidance to develop constructs with microscale architecture for improved chondrogenesis and function. Stable channels of varying microscale dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 34 publications
6
23
1
Order By: Relevance
“…This correlates well with other studies, where cartilage repair was attributed to cell homing, engraftment and repair due to pore architecture of the construct used. 4,9,19 Despite that collagen type I staining was observed in all defects in the present study, chondrocytes adjacent to the cell-free construct did not stain positive. Although, collagen type I is associated with fibrocartilage repair, spatial and temporal patterns of collagen type I expression have been observed during cartilage development, 26 at early time points during in vitro chondrogenesis of MSC 14 and after ACI in humans.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…This correlates well with other studies, where cartilage repair was attributed to cell homing, engraftment and repair due to pore architecture of the construct used. 4,9,19 Despite that collagen type I staining was observed in all defects in the present study, chondrocytes adjacent to the cell-free construct did not stain positive. Although, collagen type I is associated with fibrocartilage repair, spatial and temporal patterns of collagen type I expression have been observed during cartilage development, 26 at early time points during in vitro chondrogenesis of MSC 14 and after ACI in humans.…”
Section: Discussioncontrasting
confidence: 67%
“…1A illustrateds the generation of a biomimetic pore structure, with an open tunnel system, created by the customdesigned layer structure. In addition to creating an open functionally-graded pore template for cells that complements the work of Chou et al 4 and Lee et al, 19 the compressive modulus values were orders of magnitude higher (10 MPa) than previous composite constructs 27 (0.005-0.10 MPa) and represent a step towards mechanical property values proposed for hyaline cartilage regeneration in the region 1-12MPa. 12 However, it must be noted that compression testing of the macroporous PLCL scaffolds was performed on dry samples at room temperature and that future studies will be conducted to examine the mechanical properties of constructs stored 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Previous studies have successfully employed bone marrow-derived MSCs for cartilage repair applications.…”
Section: Discussionmentioning
confidence: 67%
“…Further, exposure to TGF-β1 gradients led to chondrogenesis. These results, together with a previous study that showed that aligned MSCs produce aligned collagen, suggest that oriented cartilage tissue structures with superior mechanical properties can be obtained by using flow and chondrogenic factor gradients formed by microfluidics [19].…”
Section: Introductionsupporting
confidence: 73%
“…The primary antibody host species is mouse and the antigen species is chicken. It has been shown to have cross-reactivity with human type II collagen [19,31] synthesized by human MSCs. The samples were then washed in PBS for 1 h. FITC-conjugated goat anti-mouse IgG, diluted 1:500 in 1% NGS, was then applied to the aggregates for 45 min.…”
Section: Type II Collagen Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation